Employee Performance: Organizational Culture, Discipline and the Mediating Role of Motivation - Suparman, Dadang; Purnama, Reka Ardian; Naryono, Endang (Economics and Digital Business Review, 2023)
The success of an organization in industry 4.0 towards the era of society 5.0, not separated from thestrength and clarity of organizational culture and work discipline rules, because these two factors can trigger employee motivation, focus and be able to maximize abilities so that they can achieve their best performance. The purpose of this study is to examine and analyze the mediating role of motivation (Mv) in the relationship between organizational culture (OC) and work discipline (WD) in influencing employee performance (EP). Purposive sampling technique was chosen, primary data obtained from the responses of 48 Respondents processed using SPSS v26. Analysis method with simple path analysis model. The findings of the study, structural I showed that OC and WD had a significant positive effect on Mv. Structural II, shows that OC and WD have a significant positive effect on EP both directly and indirectly through Mv. Mv has been shown to have a mediating effect on the relationship of OC and WD in influencing EP. Indirect effect OC to EP through Mv is greater than direct effect OC to EP, as well as indirect WD to EP through Mv so that the total effect of all lines in the model becomes greater on EP. Modification and development of OC as a form of innovation and adaptation of the organization's journey potentially needs to be done to find alignment of employee behavior in the organization towards a better EP in line with work challenges in industry 4.0. This still requires investigation.